Acceptability and safety of novel infant porridges containing lyophilized meat powder and iron-fortified wheat flour - Pachón, Helena; Liria Domínguez, M.R.; Creed-Kanashiro, Hilary M.; Stoltzfus, RJ (2007)
BACKGROUND: Lyophilized meat powder with iron-fortified wheat flour can be used to produce an infant porridge with bioavailable iron, but its acceptability and safety are unknown. OBJECTIVE: To evaluate the acceptability and safety of porridges containing lyophilized meat powder and iron-fortified wheat flour. METHODS: Peruvian mothers' input was used to develop porridges without (no meat) and with meat powder (low or high chicken liver, low or high chicken thigh). Acceptability was determined by maternal hedonic scoring, 9-day infant intake, and videotape analysis of how well infants liked each porridge. Dry and cooked porridges and meat ingredients were tested for microorganisms; meats were tested for pesticides. RESULTS: Mothers gave higher acceptability scores to the no-meat porridge, followed in order by low and high quantities of meat powder (e.g., mean +/- SD "taste"scores were 4.5 +/- 0.9 for the no-meat, 3.7 +/- 1.1 for the low-liver, and 3.3 +/- 1.1 for the high-liver porridges, p = .0001). Infants' porridge intake did not differ: 61.4 +/- 47.1 g of no-meat, 62.1 +/- 44.9 g of low-thigh, and 67.5 +/- 42.0 g of low-liver (p = .7), as supported by the video analysis. Microbiologic safety was acceptable except for marginally acceptable molds and yeasts in dry ingredients. No pesticide residues were detected. CONCLUSIONS: Despite mothers' clear preference for no-meat porridges, infants consumed equal amounts of porridges with and without meat. Thus, if mothers can be convinced to feed the meat-containing porridges to the infants despite their own preferences, the infants will consume these porridges. The mold and yeast content of the porridge ingredients must be reduced.